Bioconcentration of Chrome (Cr) Metal in Three Types of Sponge (Callispongia sp., Xetospongsia sp. and Petrosia sp.) from Ambon Bay - Siahaya, Antho Netty; Noor, Alfian; Joris, Shielda Natalia (Indonesian Journal of Chemical Research, 2021)
Research about bioconcentration of Chrome metal in three types of sponge (Callispongia sp., Xetospongia sp., and Petrosia sp.) from Ambon Bay. This research main is to know the most effective type to accumulate Cr metal in water. The Cr concentration measurement of water, sediment, and sponges at each location shows that metal concentration is 0.001-0.030 ppm in sediment higher than 0.001-0.003 ppm in water. Concentration based on sponges type Callispongia sp., Xetospongia sp., and Petrosia sp. are 0.001-0.262 mg/kg dry weight: 0.001-0.134 mg/kg dry weight, 0.001-0.330 mg/kg dry weight, respectively. The adsorption factor (AF) of Cr metal ranges from 0.000-0.028 ppm. Bioconcentration factor (BCF) based on sponges type Callispongia sp., Xetospongia sp., and Petrosia sp. are -0.011-0.261 mg/kg dry weight, -0.001-0.132 mg/kg dry weight, and -0.001-0.329 mg/kg weight dry, respectively. Sponges type that suitable used as Cr metal pollution monitoring media is Callispongia sp. and Xetospongia sp.